Impact of surgical consultation and counseling on patients perspectives regarding nasal shape and expectations from rhinoplasty - Georges Ziade; Georges Abikanaan; Dayane Daou; Desiree Karam; Elias Keyrouz; Rami Saade (Advances in Oral and Maxillofacial Surgery)
Background and objectives: Surgical rhinoplasty is a challenging aesthetic procedure, where patient satisfaction is the primary measure of success. This study assessed patients' perceptions of their nose shapes before and after a surgical consultation, using the Face-Q questionnaire. Materials and methods: Patients attending preoperative consultations for primary rhinoplasty completed the Face-Q questionnaire; additional questions included those on nasal symmetry and skin regularity. Subsequently, the same questions were answered after standardized clinical assessment-based photos and measurements. The two sets of answers and demographic data analysis were compared. The study group was stratified by age into younger than or equal to, and older than 21 years, and compared using previously mentioned statistical methods. Results: Forty patients, predominantly women (65 %), with a mean age of 26.5 years, were included. The Face-Q scores significantly changed after the objective assessment (mean change 3.30, p < 0.001). Stratification by age showed statistically significant differences in all questions for participants above 21, while those below 21 exhibited significant changes in all questions except those on columellar symmetry. Conclusion: A preoperative review of a rhinoplasty patient's own nasal features through photographs influenced their perception of their nose, highlighting the importance of preoperative counseling in managing patient expectations effectively.